Prevalence of oral cancer and pre-cancer and associated risk factors among tea estate workers in the central Sri Lanka - Ariyawardana, A.; Sitheeque, M. A. M.; Ranasinghe, A. W.; Perera, I.; Tilakaratne, W. M.; Amaratunga, E. A. P. D.; Yang, Yi-Hsin; Warnakulasuriya, S. (Journal of oral pathology & medicine, 2007)
Background:  To screen for oral cancer or not is being debated, but for high‐risk populations with minimal access to regular dental care systematic oral examinations could provide some benefit. Methods:  We undertook oral mucosal examinations of labourers employed in tea estate plantations in Sri Lanka. In a two‐stage screening procedure, first by estate medical officers and then by visiting specialists, we examined 12 716 persons at their workplaces achieving a coverage of one‐sixth of the total workforce. Results:  Fourteen oral cancers and 848 subjects with oral pre‐cancer (6.7%) were detected giving population prevalences of 46.1 per 1000 for leukoplakia and 16.4 per 1000 for oral submucous fibrosis. Among subjects with any oral mucosal disorder (n = 1159) proportions of current users of betel quid, smokers and alcohol use was recorded at 92%, 31% and 61% respectively. The synergistic effect of these three risk habits on the development of oral leukoplakia was evident in mixed habit groups. Conclusions:  The prevalence of oral pre‐cancer in tea estate labourers was higher than estimates reported in previous studies. In the absence of state‐sponsored preventive activities, it is necessary to improve the capacity of individual health practitioners and small medical centres to participate in oral health promotion and oral cancer/pre‐cancer screening.